Overview of Risk Factors for Cholelytasis Patients at Royal Prima Medan Hospital in 2022-2023 - Syakira Iatassomi; Ferdinando Motuho Baeha; Cut Elvira Novita (International Journal Labs, 2025)
This study aims to provide an overview of the risk factors associated with cholelithiasis among patients treated at Royal Prima Hospital Medan during 2022–2023. Using a quantitative approach with a cross-sectional design, data were collected simultaneously from patient medical records to identify and describe risk characteristics. The research population included all patients diagnosed with cholelithiasis within the specified period, while the sampling technique employed was proportional random sampling. Data were obtained through documentation methods and analyzed using univariate descriptive statistics to present the distribution of each variable. The findings revealed that the majority of patients were female (59.7%), aged over 40 years (68.1%), had a family history of cholelithiasis (90.3%), and were overweight (45.8%). Body mass index (BMI) analysis showed that 45.8% of patients were overweight, 36.1% had normal BMI, and 18.1% were obese, with no underweight cases identified. The results are expected to highlight key factors such as age range, body mass index (BMI), and family medical history contributing to the occurrence of cholelithiasis. This study provides valuable insights for healthcare providers in improving preventive strategies and promoting public awareness regarding the risk factors for cholelithiasis.